2017
DOI: 10.1111/josh.12547
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and HIV Risk Among High School Teenagers: The Mediating Role of Teen Dating Violence

Abstract: Our findings suggest that multidimensional interventions should be developed to reduce the rate of teen dating violence and combat bullying as a preventative method for HIV risk among high school students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(47 reference statements)
0
13
2
Order By: Relevance
“…was not directly associated with STIs, which was incongruent with the past research findings (Kamen et al, 2013;Okumu et al, 2017;Russell et al, 2011). It is unlikely that bullied youths immediately acquire STIs; rather, there are several mechanisms linking peer victimization and STIs, which require further exploration.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…was not directly associated with STIs, which was incongruent with the past research findings (Kamen et al, 2013;Okumu et al, 2017;Russell et al, 2011). It is unlikely that bullied youths immediately acquire STIs; rather, there are several mechanisms linking peer victimization and STIs, which require further exploration.…”
Section: Discussioncontrasting
confidence: 77%
“…Numerous studies have documented that peer victimization during childhood is a precursor to risk behaviors, such as substance use. Despite extant cross-sectional and longitudinal studies that have revealed that bullied youth have an elevated risk of acquiring STIs and HIV during adolescence (Okumu, Mengo, Ombayo, & Small, 2017) and adulthood (Friedman, Marshall, Stall, Cheong, & Wright, 2008; Kamen et al, 2013; Russell, Ryan, Toomey, Diaz, & Sanchez, 2011), research examining the link between peer victimization and STIs is limited. Okumu et al’s (2017) findings from a nationally representative sample of 13,571 youths in Grades 9 to 12 suggest a significant positive association between bullying experiences and HIV risks.…”
Section: Exploring the Link Between Peer Victimization And Sti Acquismentioning
confidence: 99%
“…Adolescents who are bullied are more likely to have multiple sexual partners, have sex without a condom, use substances, and experience depression. 4,[13][14][15][16][17] Addressed separately, these four focus areas are of concern to public health. However, data also indicate that risk behaviors co-occur and that a substantial minority of students have experienced multiple risks across these areas.…”
Section: Why Cdc Focuses On These Priority Health Areasmentioning
confidence: 99%
“…26 Research suggests adolescents who are bullied, whether at school or electronically, are more likely to have multiple sexual partners, to have sex without a condom, to use substances, and to experience depression. 4,[13][14][15][16][17] Forced sex is directly related to HIV and STD risk, 29 but it is also related to the experience of trauma, leading to substance use, mental health problems, and suicide risk. 30 Physical and sexual dating violence may have similar impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying, both perpetration and victimization, has been associated with sexual risk behaviors such as early sexual behavior, sex under the influence of substances, failure to use a condom, and multiple sex partners (Connolly et al, 2000; Hertz et al, 2015; Holt et al, 2013; Hong et al, 2016; Okumu et al, 2017). Sexual minority youth have been shown to experience higher rates of bullying (e.g., Holt et al, 2013; Nansel et al, 2001; Toomey & Russell, 2016).…”
Section: Introductionmentioning
confidence: 99%